Reading and controlling the text - Loader, James Alfred (Old Testament essays, 2006)
It is argued that not only 'colonialists' or powerful establishments use the control of texts in their own interests, but that this is also done by religious groups at the other end of the power spectrum. Those who resist 'imperialist' or 'colonialist' powers, often revert to text control in order to entrench the way in which those texts are read. They manipulate the meaning of the text by curtailing alternative reading possibilities and therefore seek to wield power over the reader in order to achieve their own ends. Three examples are given: the tradition in which the Masoretic network flourished, typical Protestant use of the Bible as antidote to papal hegemony, and more recent Liberation Theology as a system of resistance to colonialist hegemony. Concluding thoughts are offered on the meaning of tolerance in this regard and the ethics of scholarly discourse pertaining to the control of texts.